Partial regularity results of minimizers of quasiconvex functionals of higher order - Kronz, Manfred (Annales de l'Institut Henri Poincaré - Analyse Non Linéaire, 2002)
We consider minimizers u∈Wm,p(Ω,RN) of uniformly strictly quasiconvex functionals F(u)=∫Ωf(D mu)dℒn of higher order. Here Ω is a domain in Rn, m ≥ 1, and f is a C2-integrand with growth of order p, p ≥ 2. Using the technique of harmonic approximation we give a direct proof of almost everywhere Cm,α-regularity for such minimizers. © 2002 Éditions scientifiques et médicales Elsevier SAS.
UnivIS-Import:2015-03-09:Pub.2002.nat.dma.lma2.partia